Decentralized production and public liquidity with private information - David C. Nachman; Stephen D. Smith (Federal Reserve Bank of Atlanta, 2000)
Firms with private information about the outcomes of production under uncertainty may face capital (liquidity) constraints that prevent them from attaining efficient levels of investment in a world with costly and/or imperfect monitoring. As an alternative, we examine the efficiency of a simple pooling scheme designed to provide a public (cooperative) supply of liquidity that results in the first best outcome for economic growth. We show that if, absent aggregate uncertainty, the elasticity of scale of the production technology is sufficiently small, then efficient levels of investment and growth can always be supported. Finally, some results for a special case (constant elasticity of scale) are examined when investors face aggregate uncertainty. We show that, in addition to a low elasticity of scale for the production function, investors must have sufficiently optimistic prior beliefs if efficient growth is to be achieved regardless of the actual future state of the world.
Keywords: 330; Information theory; Liquidity (Economics); Production (Economic theory)